The Relation Between Information Asymmetry and Firm Value: Empirical Evidence from Vietnamese Listed Firms - Thai, Nguyen Hoang; Phuong, Do Ngoc; Hong, Nguyen Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2021)
Managers normally have an advantage over the market in predicting firm-specific events. This creates information asymmetry between managers of the firm and the market. The purpose of this paper is to investigate the relationship between firm value and information asymmetry in Vietnam. Our data include 202 non-financial companies with 606 firm-year observations collected from the two main stock exchange markets in Vietnam including Hanoi Stock Exchange and Ho Chi Minh Stock Exchange, covering 3 years from 2017-2019. The finding of this study indicates that two variables measuring information asymmetry (ASYDISP, ASYDUM) negatively impact firm value. Besides, control variables such as return on assets, leverage, firm size, and intangible assets are found to have significant effects on firm value.